APPLICATION OF THE BOOK OF FUTŪḤUL MANNĀN IN LEARNING NAHWU SHOROF AT SYEKH MUHAMMAD JA'FAR Islamic Boarding School BANYORANG VILLAGE TOMPOBULU DISTRICT BANTAENG DISTRICT - Ahmad Zaini (JICSA : Journal of Islamic Civilization in Southeast Asian, 2023)
Article This fall For discuss Application of Kitāb Futūḥul Mannān in Learning Nahwu Shorof at the Syekh Muhammad Ja'far Islamic Boarding School, Banyorang Village, Tompobulu District Bantaeng Regency , Learning in Islamic boarding schools is very identical to the classical book called the Gundul Book (Kitab Kuning). The system used in Islamic boarding schools is still in the form of halakah. In study article This use The type of research is descriptive qualitative with a pedagogical approach. The data sources for this research use primary data (students, teachers or leaders) and secondary data such as the results of notes on daily activities and the results of notes in the field as well as other data that can be used as complementary data. Furthermore, the data collection method used is the observation method. interviews, and documentation methods. The research instruments are observation guidelines and interview guidelines. Data processing techniques include data collection, data transcription, data classification, data interpretation, and data description. Results study This suggest that educators use appropriate techniques to teach Kitāb Futūhul Mannān well so that students are able to understand the rules of nahwu Shorof so that it is easy to read the yellow book. Supporting factors in the application of kitāb futūhul mannān in learning nahwu Shorof at the Syekh Muhammad Islamic Boarding School, Banyorang Village, Tompobulu District, Bantaeng Regency is the method used to quickly learn to read the yellow book, from the teacher/tutor side it is the result of selection who have extensive expertise in the field of Nahwu Shorof and in terms of good environment and facilities. The inhibiting factor is the lack of study hours which results in less extensive explanations, which often happens activities simultaneously so that sometimes tutors have to stop learning and there is a lack of coordination between tutors and Islamic boarding school administrators, especially Islamic boarding school leaders.